Short-term consumption of probiotic lactobacilli has no effect on acid production of supragingival plaque - Marttinen, Aino; Haukioja, Anna; Karjalainen, Sára; Nylund, Lotta; Satokari, Reetta; Öhman, Carina; Holgerson, Pernilla; Twetman, Svante; Söderling, Eva (Clinical oral investigations, 2012)
Acidogenicity and the levels of mutans streptococci (MS) in dental plaque after the use of Lactobacillus rhamnosus GG (LGG) and Lactobacillus reuteri were determined. The study had a randomised, double-blind, crossover design. Thirteen volunteers used tablets containing LGG or a combination of L. reuteri SD2112 and PTA 5289 for 2 weeks. At baseline and at the end of each tablet period, all available supragingival plaque was collected. Lactic acid production was determined from a fixed volume (8 μl) of fresh plaque and the rest of the plaque was used for culturing MS and lactobacilli. The retention of probiotics to the plaque was assessed using PCR techniques. No probiotic-induced changes were found in the acidogenicity of plaque. Also, MS counts remained at the original level. The number of subjects with lactobacilli in plaque increased in the L. reuteri group ( p = 0.011) but not in the LGG group. PCR analysis of plaque revealed the presence of LGG in four and L. reuteri in six subjects after the use of the probiotic. The use of the lactobacilli did not affect the acidogenicity or MS levels of plaque. Short-term consumption of LGG and L. reuteri appeared not to influence the acidogenicity of plaque.